1997
DOI: 10.1108/09578239710156971
|View full text |Cite
|
Sign up to set email alerts
|

Coping with stress in the principalship

Abstract: School principals face very busy and highly unpredictable work days with many individuals and groups competing for their time. Roberson and Matthews write that many principals are overworked, constantly under fire, and unappreciated [1]. Fallon states that confrontation, conflict, and compromise are constants which principals face on a daily basis [2]. Gmelch asserts that principals are becoming increasingly faced with more pressure, more aggression, more change, and more conflict than ever before [3]. In Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 10 publications
3
43
0
Order By: Relevance
“…A review of some of his studies explore the topics of school administrator stress (Gmelch & Swent, 1984), coping mechanisms (Gmelch & Chan, 1982), and creation of a coping taxonomy in response to workplace stress (Gmelch, 1988). Based on his pioneering work, a large number of studies on stress in the principalship have followed over the years, in dissertations (Finaldi, 1983;Hall, 2007;Harrison, 1991;Horgen, 1991;Romney, 2012;Welmers, 2005), journal articles (Allison, 1997;Carr, 1994;Cushing, Kerrins, & Johnstone, 2003;Goodwin, Cunningham, & Childress, 2003;Whitaker, 1996) and books (Brock & Grady, 2002;Brock & Grady, 2004;Queen & Queen, 2005).In addition, a large body of research on principal stress has focused specifically on the unique challenges of female principals as they navigate the workplace (Buss, 2008;Goeller, 1995;Lucas, 2003;Shakeshaft, Nowell, & Perry, 1991;Smulyan, 2000).…”
Section: Stress In the Principalshipmentioning
confidence: 99%
“…A review of some of his studies explore the topics of school administrator stress (Gmelch & Swent, 1984), coping mechanisms (Gmelch & Chan, 1982), and creation of a coping taxonomy in response to workplace stress (Gmelch, 1988). Based on his pioneering work, a large number of studies on stress in the principalship have followed over the years, in dissertations (Finaldi, 1983;Hall, 2007;Harrison, 1991;Horgen, 1991;Romney, 2012;Welmers, 2005), journal articles (Allison, 1997;Carr, 1994;Cushing, Kerrins, & Johnstone, 2003;Goodwin, Cunningham, & Childress, 2003;Whitaker, 1996) and books (Brock & Grady, 2002;Brock & Grady, 2004;Queen & Queen, 2005).In addition, a large body of research on principal stress has focused specifically on the unique challenges of female principals as they navigate the workplace (Buss, 2008;Goeller, 1995;Lucas, 2003;Shakeshaft, Nowell, & Perry, 1991;Smulyan, 2000).…”
Section: Stress In the Principalshipmentioning
confidence: 99%
“…Research done almost two decades ago by Allison (1997) looked at the relationship between different coping preferences and stress levels of school principals in Canada. The results from the study found that suitable coping strategies lead to less stress experience.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Roesch (1979) preformed a comprehensive study on relationship between degree of stress and coping preferences among elementary school principals. Allison (1997) identified the most common coping techniques utilized by public school principals to ameliorate the effects of stress and clustered these coping techniques into interpretable and meaningful coping categories. He determined whether there were any differences in the number of coping techniques most frequently utilized by principals or not.…”
Section: Introductionmentioning
confidence: 99%